ANALYSIS OF MUKHĀBARAH PRACTICES IN THE TUMPANG SARI SYSTEM IN ASAHAN REGENCY FROM THE PERSPECTIVE OF THE SHAFI'I SCHOOL OF THOUGHT - Sahliah, Sahliah (AT-TAFAHUM: Journal of Islamic Law, 2024)
intercropping is a popular farming method in agrarian societies, where two or more types of crops are planted together or alternately. This system supports agricultural intensification, which is to increase yields by optimizing existing land. Intercropping should not be a problem if it is done on legal land with permits and profit-sharing agreements. However, Asahan Regency often does not comply with the rules of the Shafi'i madhhab. In fact, the residents are residents of the Shafi'i madhhab. However, they do not apply Fiqh Shafi'i. Residents asked permission from the land ranger without the knowledge of the owner who lives in the city and rarely visits. This permit is given without a contract, agreement, and without a clear profit-sharing agreement, which is the main problem. This study aims to examine the practice of mukhabarah contracts on intercropping according to madhhab Shafi'i in Asahan Regency, understand the views of the community, and analyze their legal position. This study uses an empirical juridical method with data collection through document studies, observations, interviews, and secondary data. From this, 3 research conclusions were found, namely first, the practice of intercropping in Asahan Regency is not in accordance with the Shafi'i madhhab because permits are only given to land guards orally, without documentation, and without a clear profit-sharing agreement. Second, the community considers intercropping cooperation normal even though it often violates the rules due to land limitations. Third, the mukhabarah contract in Asahan Regency is not in accordance with the provisions of the Syafi'iyah ulama because it is made without involving the land owner and without a clear agreement on the time of use, the distribution of revenue, and the provision of capital